Capacitación docente para la inclusión de niños con discapacidad auditiva en instituciones regulares - Reyes Cajape, Marjorie Cecilia (2021)
The Municipal School of Hearing and Language educates children and adolescents with hearing impairment from the Initial to Seventh Grade level of Basic General Education, provides the student with hearing impairment with comprehensive training and the basic tools that allow him to operate independently and be included in the Eighth Grade Basic General Education, opening the possibility of continuing his studies. This specialized education institution provides advice to the educational community that is committed to participating in the inclusion process. This research work: Teacher training for the inclusion of hearing impaired children in regular institutions aims to design a teacher training system that contributes to the development of professional skills in teachers for the care of hearing impaired students, in regular institutions. The study is carried out through mixed-focused research, combining the application of quantitative and qualitative methods: theoretical methods, empirical methods and statistical methods……….